PHYSIOLOGICAL RESPONSES OF FISH TO ROGOR AND ALACHLOR PART-I. GENERAL IMPACT ON HETEROPNEUSTES FOSSILIS - CHATURV, L.D.; AGRAWAL, KAVITA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1991)
For H. fossilis 50% lethal concentration values (CLC50) of rogor were found to be 12.88, 12.13, 11.40 and 10.53 ppm for 12 h, 24 h, 48 h and 96 h respectively. In case of alachlor, these were 4,717, 4.430, 4.162 and 3.732 ppm, respectively for the same duration. Relative potencies of alachlor in comparision to rogor for different time assays are 3.7305, 2.7381, 3,7391 and 3.8215. The data obtained clearly indicate that alachlor is more toxic than rogor. The fish showed specific behavioural responses to different concentrations of pesticides while prompt behavioural changes were noticed soon after the fish was introduced to the test concentration, these markedly decreased as time passed. Mortality data was plotted on a probit log paper and a straight line relationship between concentration and probit of kill was established for different time assays.